Long-term contribution of international electives for medical students to professional identity formation: a qualitative study - Masato Eto; Keiko Nanishi; Mikio Hayashi; Daisuke Son (BMJ Open)
Objectives Globalisation has given medical university students the opportunity to pursue international electives in other countries, enhancing the long-term socialisation of medical professionals. This study identified the long-term effects of international electives on the professional identity formation of medical students.Design This is a qualitative study.Setting The authors interviewed Japanese medical professionals who had completed their international electives more than 10 years ago, and analysed and interpreted the data using a social constructivism paradigm.Participants A total of 23 medical professionals (mean age 36.4 years; range 33–42 years) participated in face-to-face, semistructured in-depth interviews.Results During the data analysis, 36 themes related to professional identity formation were identified, and the resulting themes had five primary factors (perspective transformation, career design, self-development, diversity of values and leadership). It was concluded that international electives for medical students could promote reflective self-relativisation and contribute to medical professional identity formation. Additionally, such electives can encourage pursuing a specialisation and academic or non-academic work abroad. International electives for medical students could contribute to medical professional identity formation on the basis of cross-cultural understanding.Conclusions This study addressed a number of issues regarding the long-term impact of international elective experiences in various countries on the professional identity formation of Japanese medical professionals. This study offers some guidance to mentors conducting international electives and provides useful information for professional identity formation development in medical professionals.